Antibiotic use in goats: role of experience and education of Missouri veterinarians. (21st March 2020) - Landfried, Lauren; Pithua, Patrick; Lewis, Roger D; Rigdon, Steven; Jacoby, Jonathan; King, Christopher C; Barnidge, Ellen K; Baskin, Carole R
Abstract : Background: In a previous study, we found that rates of antibiotic residues in goat carcasses in Missouri were three times the published national average, warranting further research in this area. Methods: We conducted a cross‐sectional survey of goat veterinarians to determine attitudes and practices regarding antibiotics, recruiting 725 veterinarians listed on the American Association of Small Ruminant Practitioners (AASRP) website and 64 Missouri Veterinary Medical Association (MVMA) veterinarians. Results: We collected 189 responses (26.1%) from AASRP members (170 valid) and 8 (12.5%) from MVMA veterinarians totalling 178 responses. While the vast majority of all veterinarians indicated that they prescribed antibiotics less than half of the time, Missouri veterinarians indicated that they spent more time treating goats for overt disease like intestinal parasites and less time on proactive practices such as reproductive herd health management comparatively. While veterinarians agreed that antibiotic resistance was a growing concern, veterinarians outside of Missouri seemed more confident that their own prescription practices was not a contributor. Although nationally most veterinarians felt that attending continuing education classes was beneficial, 73.4% in other states attended classes on antibiotic use compared to only four of the nine Missouri veterinarians. Conclusion: Missouri veterinarians had less veterinary experience than veterinarians in other states, and this, in conjunction with low continuing education requirements in Missouri relative to most other states, may hinder development of more proactive and effective client–veterinary relationships.